CHANGES IN HYDRATED ETHANOL AND REGULAR GASOLINE PRICES DURING THE COVID-19 PANDEMIC PERIOD - Soares Borges, Otávio; Ferrarezi Junior, Edemar; Alexandre Cavichioli, Fábio (Revista Interface Tecnológica, 2023)
The Covid-19 health crisis, in line with the war between Russia and Ukraine, brought significant changes in all sectors of the economy, including with regard to the prices of consumer goods and services. Therefore, the objective of this article is to identify the price variations of hydrated ethanol in relation to the prices of regular gasoline, covering the period between 2020 and 2022 and taking into account the Covid-19 scenario. To this end, bibliographic research was defined as a methodology. The results demonstrated that there were fluctuations in the prices of both hydrated ethanol and regular gasoline, and that even in the year 2020, driven by the reduction in consumption and social distancing, prices reduced, and in the years 2021 and 2022, with the opening of the economy, these prices became high again. However, it was possible to consider that the serious pandemic crisis, as it is an atypical situation, as well as others that may occur, requires records of changes in consumption and prices related to fuels and biofuels, particularly ethanol and gasoline, and with this, management decisions are made related to production costs at the plants, and government policies to control prices due to the dependence of more than 60% on road freight in Brazil.